The Global Society and Its Enemies - Kühnhardt, Ludger. author. aut Link
VIII, 276 p.
Keywords: This book discusses contemporary constellations of international politics and global transformation. It offers guidance on how to conceptualize the complexity of current global changes and practical policy advice in order to promote an open global society. In the light of today’s challenges, the author re-interprets the main argument of the philosopher Karl Popper in "The Open Society and Its Enemies". Based on this framework and new empirical evidence, the book discusses the thesis of an ongoing Third World War, triggered by fundamental deficits in nation-building, occurring primarily within states and not between them, and accelerated by asymmetric forms of warfare and Islamist totalitarianism. The book also explores various threats to the global order, such as the paradox of borders as barriers and bridges, the global effects of the youth bubble in many developing countries, and the misuse of religious interpretation for the use of political violence. Lastly, the author identifies advocates and supporters of a liberal, multilateral and open order and argues for a reinvention of the Western world to contribute to a revival of a liberal global order, based on mutual respect and joint leadership.